DIVERSITY OF THE PARASITOID WASPS OF THE EULOPHTD SUBFAMILY EULOPHINAE (INSECTA: HYMENOPTERA, EULOPHIDAE) OF JAVA, INDONESIA AND THEIR DISTRIBUTION - Ubaidillah, Rosichon (Research Center for Biology-Indonesian Institute of Sciences, 2007)
Diversity of the Parasitoid Wasps of the Eulophid Subfamily Eulophinae (Insecta: Hymenoptera, Eulophidae) of Java, Indonesia and their distribution is presented for the first time. Most of eulophines are ectoparasitoids that attack concealed hosts in protected situations, such as leafminers, woodborers and leaf rollers. The subfamily are frequently involved in biological control programs directed against dipteran and lepidopteran leaf-mining pests, and many eulophine genera have been considered economically important. The taxonomy and distribution of the species in Asia, especially in Java, are however still poorly studied despite the fact that the subfamily is an important group for sustainable agriculture. This study is based on the specimens newly collected from many localities in Java and Bali using sweep netting, Malaise trapping, yellow-pan trapping and rearing from their hosts. All the three tribes (Elasmini, Cirrospilini and Eulophini) of the subfamily Eulophinae are recognized in the islands.A single genus of Elamini, three genera of Cirrospilini and 19 genera of Eulophini are recognized in the islands and they included 14 genera as new records for the islands and 66 undescribed species. A total of 110 species are recognized in Java and Bali; of those about 86% are new records for the islands and about 60% are undescribed species. Considering the species so far known for their world distribution pattern, eulophine species occurring in Java are mainly Oriental elements, a few species are Australian and a very small number of species is endemic, while several species that could have been artificially introduced with their hosts are worldwide in their distribution. Based on the climatic and geological features, the species diversity and geographical distribution of the Eulophine in Java and neighboring island are discussed.